The Influence of Service Quality and Price on User Satisfaction of Food Delivery Service Application In Palembang City - Suhalim, Shinta Putri; Dewi, Tri Wahyuni T; Yanti, Desma (Jurnal Pemasaran Kompetitif, 2024)
The purpose of this study is to see whether service quality and price affect customer satisfaction. The sampling method used non probability sampling, namely the purposive sampling method. the sample in this study were 110 respondents. Data was collected using an online questionnaire (google form) distributed via social media. Based on the findings of this study, service quality and price have a positive and significant effect on user satisfaction of food delivery service applications in Palembang City.